The teaching of history from within the armed conflict in northwestern Mexico (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2023)
At the international level, the growing interest in education for democratic citizenship indicates a variation in the order and importance of educational purposes, directs our gaze towards the possible future and the creation of fairer and more peaceful societies. This transition has not yet occurred in Mexico and is inserted in a context of armed violence and disintegration of the social fabric that demonstrates the inability of the State to guarantee security and respect for human rights. Although multidimensional factors are combined in the generation of violence, it is nonetheless urgent to assume a commitment from school education and modify training priorities to respond to one of the most pressing problems facing the country. With this objective, the research seeks to contribute from the history didactics to the promotion of coexistence, peace, and democratic participation. In this order, the study includes a consultation with high school students, teacher students and in-service teachers to find out their willingness to change, an account of the difficulties and opportunities to teach controversial topics in the classroom is made, three proposals that can help build the future, as well as a decalogue of rights and duties when teaching armed conflict.
Keywords: armed conflict, culture of peace, history didactics, commitment of teachers